The process of cancer. Part II. Selected plant compounds in cancer. Chemoprevention - Jopkiewicz, Sylwia Paulina (Journal of Education, Health and Sport, 2019)
Summary: Introduction and objective:Constantly increasing number of cancers, as well as too low efficiency of the treatment of advanced stages of the disease implies the search for effective action both in terms of primary prevention and secondary. The article comp is only an outline of selected compounds share vegetable chemoprevention of cancer. Its aim is to introduce the concept of chemoprevention and discussion of selected plant compounds and their impact on the process of carcinogenesis.Description of knowledge:Method of connecting primary and secondary prevention is cancer chemoprevention. It uses natural and synthetic compounds to inhibit, delay or reverse the neoplastic process.Glucosinolates found in cruciferous vegetables have potent biological properties applicable to the prevention of the carcinogenesis process. The best-known glucosinolates are sulforaphane and indole -3-carbinol. Curcumin is a natural agent having a broad antitumor effect. It is among the blocking and suppressive chemopreventive agents. Inhibits activation of cancer gene, tumor growth, cell proliferation and angiogenesis. Resveratrol shows efficacy in blocking all stages of carcinogenesis, while lycopene is a powerful antioxidant, which inactivates free radicals thereby reducing the DNA damage of the cell.Conclusions: Chemoprevention is a method which may intervene in all stages of carcinogenesis, and the largest of its efficacy is observed in the initiation and promotion of cancer lesions. Some food ingredients have both a anticarcinogenic and cytostatic effects on cancer cells.